Phenolic Contents and Antioxidant Properties of Bauhinia rufescens, Ocimum basilicum and Salvadora persica, Used as Medicinal Plants in Chad - Hissein Hassan Abdel-razakh; Gaymary George Bakari; Jin-Soo Park; Cheol-Ho Pan; Abubakar Shaaban Hoza (Molecules)
The plants Bauhinia rufescens, Ocimum basilicum and Salvadora persica are well known in traditional African medicine, and particularly in traditional Chadian medicine. They are commonly used to treat infectious diseases, inflammatory diseases, fevers, gastroenteritis and other medical conditions. The aim of this study was to perform a phytochemical screening to determine the antioxidant properties of different extracts and fractions from the three plants. Ethanolic extracts and solvent fractions were prepared and analyzed for total phenolic content (TPC), total flavonoid content (TFC) and total tannin content (TTC). LC-MS and an online screening HPLC-ABTS system identified phytochemicals with antioxidant activities. DPPH and ABTS reduction methods were used to test the extracts and fractions for their antioxidant potential. The results showed that the TPC of O. basilicum was higher than that of B. rufescens, ranging from 64.70 ± 5.2 to 411.16 ± 8.11 mgGAE/g DW. B. rufescens extracts and fractions, on the other hand, showed higher TFC, ranging from 69.5 ± 5.3 to 408.26 ± 8.42 mgQE/g DW, and higher TTC, ranging from 4.57 ± 2.45 to 62.19 ± 4.7 mgTAE/g DW. The maximum TPC, TFC and TTC in both plants were recorded in the ethyl acetate fractions. S. persica extracts and fractions showed a very low quantity of TPC, TFC and TTC. Based on LC-MS and HPLC-ABTS analysis, rosmarinic acid was identified as the major component in the extracts and all fractions of O. basilicum, and epicatechin, procyanidin B and quercetin were found in B. rufescens. S. persica did not exhibit specific substances with antioxidant activity and was therefore not considered for further assays. DPPH and ABTS results showed that ethyl acetate fractions of B. rufescens and O. basilicum have the strongest antioxidant activities. This study indicates that B. rufescens and O. basilicum are good sources of phytochemicals with antioxidant properties, suitable for medicinal use in Chadian communities. Additionally, the antioxidant-rich extracts from these plants hold significant potential for cosmetic development, enhancing skin health and protecting against oxidative-stress-induced damage.